Utilization of Sandy Soil as the Primary Raw Material in Production of Unfired Bricks - Guilan Tao; Yuepeng Pan; Zhaoyang Qiao; Chaohua Jiang (Advances in Materials Science and Engineering)
In this study, attempts were made to use sandy soil as the main raw material in making unfired bricks. The sprayed-cured brick specimens were tested for compressive and flexural strength, rate of water absorption, percentage of voids, bulk density, freezing/thawing, and water immersion resistance. In addition, the microstructures of the specimens were also studied using scanning electron microscope (SEM) and X-ray diffraction (XRD) technique. The test results show that unfired brick specimens with the addition of ground-granulated blast-furnace slag (GGBS) tend to achieve better mechanical properties when compared with the specimens that added cement alone, with GGBS correcting particle size distribution and contributing to the pozzolanic reactions and the pore-filling effects. The test specimens with the appropriate addition of cement, GGBS, quicklime, and gypsum are dense and show a low water absorption rate, a low percentage of voids, and an excellent freezing/thawing and water immersion resistance. The SEM observation and XRD analysis verify the formation of hydrate products C–S–H and ettringite, providing a better explanation of the mechanical and physical behavior and durability of the derived unfired bricks. The results obtained suggest that there is a technical approach for the high-efficient comprehensive utilization of sandy soil and provide increased economic and environmental benefits.